Experimental study on the effect of Zirconia nanoparticles on solidification heat transfer characteristics: A comparison with Titania nanoparticles. (May 2018) - Aslani, Hoda; Moghiman, Mohammad
Highlights: We experimentally study the solidification behavior of ZrO2 nanofluids. We compared supercooling degree and solidification time of ZrO2 & TiO2 nanofluids. We investigate the effect of PVP as surfactant on solidification characteristics. ZrO2 nanofluid provides faster solid layers formation than TiO2 nanofluid. Abstract: In this study, the influence of Zirconia (ZrO2 ) and Titania (TiO2 ) nanopaticles on liquid–solid phase transition of aqueous nanofluids with/without Poly vinyl pyrrolidone as surfactant are experimentally compared. A cooling generation apparatus based on the compression refrigeration cycle has been used to explore the solidification behavior of nanofluids as phase change materials. The experimental results show that ZrO2 and TiO2 nanoparticles considerably reduce the solidification supercooling degree of deionized water (as basefluid). Only adding 0.04 wt% ZrO2 and TiO2 nanoparticles to base fluid, the percentage of reduction in supercooling degree attained 81% and 65%, respectively. The results reveal that although the presence of surfactant in nanofluids reduces the supercooling degree and slightly solidification time of both ZrO2 and TiO2 nanofluids; but it has no influence on onset nucleation time. Comparison of ZrO2 and TiO2 nanofluids with/without surfactant presents that ZrO2 provides faster solid layers formation and has more energy saving potential in storage systems due to its lower supercooling degree.